Protein structure model refinement in CASP12 using short and long molecular dynamics simulations in implicit solvent. (1st September 2017) - Terashi, Genki; Kihara, Daisuke
Abstract: Protein structure prediction has matured over years, particularly those which use structure templates for building a model. It can build a model with correct overall conformation in cases where appropriate templates are available. Models with the correct topology can be practically useful for limited purposes that need residue‐level accuracy, but further improvement of the models can allow the models to be used in tasks that need detailed structures, such as molecular replacement in X‐ray crystallography or structure‐based drug screening. Thus, model refinement is an important final step in protein structure prediction to bridge predictions to real‐life applications. Model refinement is one of the categories in recent rounds of critical assessment of techniques in protein structure prediction (CASP) and has recently been drawing more attention due to its realized importance. Here we report our group's performance in the refinement category in CASP12. Our method is based on inexpensive short molecular dynamics (MD) simulations in implicit solvent. Our performance in CASP12 was among the top, which was consistent with the previous round, CASP11. Our method with short MD runs achieved comparable performance with other methods that used longer simulations. Detailed analyses found that improvements typically occurred in entire regions of a structure rather than only in flexible loop regions. The remaining challenge in the structure refinement includes large conformational refinement which involves substantial motions of secondary structure elements or domains.